THE IMPACT OF HOSPITAL BASED INTEGRATED MANAGEMENT OF CHILDHOOD ILLNESS TRAINING ON PEDIATRIC NURSE COMPETENCY - Fitri Haryanti; Mohammad Hakimi; Yati Sunarto; Yayi S Prabandari (Belitung Raya Foundation, Indonesia, 2018)
Background: Although the WHO strategy integrated management of childhood illness (IMCI) for primary care has been implemented in over 100 countries, there is less global experience with hospital-based IMCI training. Until recently, no training had been done in Indonesia, and globally there has been limited experience of the role of IMCI in rebuilding health systems after complex emergencies. Objective: We aimed to examine the effect of hospital-based IMCI training on pediatric nurse competency and explore the perception of Indonesian doctors, nurse managers and pediatricians about IMCI training and its development in West Aceh, a region that was severely affected by the South-Asian tsunami in December 2004. Methods: This study used stepped wedge design. Training was conducted for 39 nurses’ staff, 13 midwives, 6 head nurses, 5 nurse managers, 5 doctors, 1 pediatrician, and 3 support facilities (nutritionist, pharmacist, laboratory) in Cut Nyak Dien (CND) Hospital in Meulaboh, West Aceh, Indonesia. The IMCI training was developed based on the WHO Pocketbook of Hospital Care for Children. A nurse’s competency questionnaire was used based on the guideline of assessment of the quality of child health services at the first level reference hospitals in districts / municipalities issued by the Ministry of Health in 2007. A linear mixed model was used for data analysis. Results: The hospital based IMCI training improved the competences of nurses pediatric in assessing emergency signs of the sick children, management of cough and difficulty breathing, diarrhea, fever, nutritional problems, supportive care, monitoring, discharge planning and follow-up. The assessment highlighted several problems in adaptation process of material training, training process and implementation in an environment soon after a major disaster. Conclusion: Hospital based IMCI training can be implemented in a setting after major disasters or internal conflict as part of a rebuilding process. The program requires strong management support and the emergency phase to be subsided. Other pre-requisites include the existence of standard operating procedures, adequate physical facilities and support for staff morale and well-being. Improving the quality of pediatric care requires more than just training and clinical guidelines; internal motivation and health worker support are essential.